基于有限长线接触弹流润滑模型的冠状修形直齿轮副接触分析 - 刘怀举; 朱才朝; 宋朝省; 林超 (Jixie chuandong)
Due to the urgent requirement of modern gear drives with high load capacity,long service life and high reliability,the gear tooth surface contact behaviour and contact fatigue behaviour are studied thoroughly. An advanced numerical model of gear contact is proposed in which the non- Newtonian lubricant,the tooth crowning modification,the variation of the gear geometry parameters,the working conditions as well as the tooth surface coating are taken into account. The effect of those factors on tooth surface contact pressure,tooth friction,film thickness and the stress of the substrate can be studied based upon this model. The proposed numerical model can not only provide a technical support for the developing of domestic design softwares of gear drives,but also it can be used for the improvement of the service lives and the reliabilities of gears after the validation with experimental results.